2005
DOI: 10.1002/jbm.a.30287
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment ability and release profile of corticosteroids from starch‐based microparticles

Abstract: Abstract:We previously described the synthesis of starchbased microparticles that were shown to be bioactive (when combined with Bioactive Glass 45S5) and noncytotoxic. To further assess their potential for biomedical applications such as controlled release, three corticosteroids with a similar basic structure-dexamethasone (DEX), 16␣-methylprednisonole (MP), and 16␣-methylprednisolone acetate (MPA)-were used as models for the entrapment and release of bioactive agents. DEX, MP, and MPA were entrapped into sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Iodine-potassium solution (Lugol) is a well-known and useful solution for chemically identifying the presence of starch molecules [31]. The amylose present in the starch molecule has a helical secondary structure [52], where substances such as iodine can lodge, forming a complex as an inclusion compound.…”
Section: Physicochemical Characterization Of Unloaded Spcl Micropartimentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine-potassium solution (Lugol) is a well-known and useful solution for chemically identifying the presence of starch molecules [31]. The amylose present in the starch molecule has a helical secondary structure [52], where substances such as iodine can lodge, forming a complex as an inclusion compound.…”
Section: Physicochemical Characterization Of Unloaded Spcl Micropartimentioning
confidence: 99%
“…For instance, starch microparticles using soluble potato starch have been developed and proposed for the release of a nonsteroidal anti-inflammatory drug [21]. Moreover, a blend of starch and polylactic acid have been used for the encapsulation of steroids, growth factors and bioactive glass in a microparticle system [31][32][33]. These studies showed that the starch-polylactic acid microparticles are suitable carriers for the controlled release of bioactive agents for bone tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Dextrans are being actively investigated for sustained delivery of therapeutic and imaging agents, particularly for injectables and colon-specific DDSs. Starch-based polymers have been proposed by Reis and Cunha (1995) as materials with potential for biomedical applications, particularly as scaffolds for bone tissue engineering applications (Gomes et al, 2001(Gomes et al, , 2002, bone cements (Espigares et al, 2002;Boesel et al, 2003) and recently as drug delivery systems Silva et al, 2005). These materials have been shown to be biocompatible in vitro (Mendes et al, 2001;Marques et al, 2002), and to possess a good in vivo performance (Mendes et al, 2003;Salgado et al, 2005).…”
Section: Incorporation and Releasementioning
confidence: 99%
“…In vitro, dexamethasone has been employed as a differentiation agent for bone marrow cells to progress into the osteoblastic lineage (Maniatopoulos et al, 1988). Within this last role, strategies employing the incorporation of dexamethasone in polymeric materials to be used as carriers for the differentiation of cells into the osteoblastic lineage have been described in the literature (Silva et al, 2005), which confers on dexamethasone a highlighted role in bone TE approaches.…”
Section: Glucocorticoidsmentioning
confidence: 99%